Energi listrik berkelanjutan: Potensi dan tantangan penyediaan energi listrik di Indonesia - Alnavis, Noviana Bayu; Wirawan, Rivaldo Restu; Solihah, Karina Indah; Nugroho, Vanadi Helmy (Institute for Advanced Science Social, and Sustainable Future, 2024)
Economic growth and increasing population density have an influence on the large need for electrical energy in Indonesia. The amount of energy needed is directly proportional to economic growth and population density. This condition could threaten energy security in Indonesia if all stakeholders still depend on non-renewable energy. Coal, oil, and natural gas, which are continuously exploited for generating electricity, will eventually run out and will no longer be able to meet Indonesia's electrical energy needs. Apart from that, the use of non-renewable energy also has a negative impact on the environment. Indonesia is a country that is rich in renewable energy sources that can be used as a source of energy for generating electricity, but there are still obstacles in processing and using them, so they are not optimal. This paper aims to analyze the potential and challenges of providing electrical energy in Indonesia. The method used is a descriptive method using primary and secondary data and literature studies. The results of this study show that the potential for renewable energy that can be processed and developed for electricity generation is quite large, namely from energy sources originating from geothermal, hydropower, mini-hydro and micro-hydro, bioenergy, solar power, wind energy, and ocean waves. The survey results show that 52% of the public agree with the use of renewable energy, and 43% agree with the use of nuclear energy as a source of renewable electrical energy. The reason for choosing nuclear energy is the reliability of the energy supply. A strategy for developing renewable electrical energy can be formulated based on the opportunities and challenges currently faced to achieve energy security in Indonesia. Efforts to develop renewable electrical energy need to be carried out with the cooperation of all relevant stakeholders so that the sustainability of electrical energy in Indonesia can be realized.